Analisis Kerusakan Perkerasan Jalan Dengan Metode Pavement Condition Index (PCI) - Atfal Nugraha Digta; Dwi Denny Apriliano; Muhammad Taufiq (CV. Rayyan Dwi Bharata, 2025)
Good road pavement is crucial to ensure smooth transportation and support economic growth and community mobility. However, over time and with high traffic volumes, road conditions can deteriorate, impacting the comfort and safety of road users. This study aims to analyze the level of pavement damage on the Tegal City Boundary – Pemalang City Boundary road section, specifically at STA. 11+000 to STA. 16+000, using the Pavement Condition Index (PCI) method. The PCI method was chosen because it is able to provide quantitative and qualitative assessments of pavement conditions based on the type and level of damage that occurs. The results of the field survey showed a variety of damage types such as alligator cracking, potholes, and raveling, with the PCI index ranging from Good to Poor. The results of this analysis are expected to be the basis for consideration in planning road maintenance effectively and efficiently.